Challenges in managing patients in Australia with chronic hepatitis B: the General Practitioners' perspective - Jack Wallace; Behzad Hajarizadeh; Jacqui Richmond; Stephen McNally (Elsevier, 2013)
Abstract Objective: General Practitioners (GPs) are essential to reducing the impact of chronic hepatitis B (CHB) given their clinical management role where only 56% of people with the infection in Australia have been diagnosed. This qualitative study aimed to identify the challenges GPs face in effectively responding to CHB. Methods: Semi‐structured interviews were conducted with 26 GPs self‐identifying as having a 'high caseload' of patients and/or a particular interest in CHB. Participants were recruited from five jurisdictions and came from diverse ethnicities, clinical experience and practice profile. Interview data were analysed according to the principles of grounded theory. Results: Patient and GP knowledge, a lack of community awareness, and language and cultural diversity impeded the GP response to CHB. Communication with specialists was reported as challenging with unclear referral pathways, limited feedback from specialists after referral, and poor liaison and support for managing people living with CHB. Regulations restricting GPs capacity to respond included the lack of prescribing opportunities, fear of Medicare auditing for screening the populations most at risk, and inadequate financial support given the complexity of CHB and the communities most affected by the infection. Conclusions: General Practitioners require additional skills and resources to support the effective management of people with CHB. These include improved awareness and knowledge about the infection, adequate financial resources to support patient management, and effective referral pathways and support.